Heat transfer enhancement in a parabolic trough collector using finned tubular absorber - Ramesh K. Donga; Suresh Kumar; Gurunadh Velidi (Scientific Reports)
Abstract This study presents an investigation into enhancing heat transfer in parabolic trough collectors (PTCs). The research focuses on improving convective heat transfer by incorporating longitudinal fins within the tubular absorber of a PTC. The study examines a PTC (parabolic trough collector) system with the following specifications: a 1.84 m focal length, a 5 m aperture width, and an absorber measuring 70 mm in outer diameter. The variable solar flux on the absorber is determined using SolTrace software. The receiver was simulated using the finite volume method. The heat flux derived from SolTrace simulations serves as a boundary condition. A comparative analysis is conducted between the findings from a parametric investigation on a standard receiver and those equipped with finned tubular absorbers. This comparison spans Reynolds numbers from 0.25 × 105 to 2.82 × 105. Studies have demonstrated that absorbers with fins substantially improve heat transfer. The tubular absorber equipped with fins shows a significant rise of 40.1% in the Nusselt number. Its performance evaluation criteria reach a peak of 1.28 when the Reynolds number is 2.82 × 105.